Christian perspective on the tolerance of Christian religious education teachers and students in the era of disruption - Arifianto, Yonatan Alex; Triposa, Reni; Saptorini, Sari (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
Amid the swift currents of globalization triggered by the explosion of the information technology revolution, conflicts often occur on issues of discrimination on race, class, and religion. Religions face challenges in resolving controversies and violent behavior and maintaining harmony between religious communities. Christian Religious Education educators need to teach their students positive responses to plurality and pluralism in Indonesia. The most important thing is the impact on students. Research using descriptive qualitative research methods concludes: first, there is a need to increase pluralism in the frame of a pluralistic society and an era of disruption. Second, believers, in this case, Christian Religious Education teachers and students, should understand pluralism from a biblical point of view. Third, Christian Religious Education teachers and students are responsible for actualizing an attitude of tolerance towards a pluralistic society both in society in everyday life and in behavior in cyberspace communities based on a biblical understanding of pluralism. Fourth, Christian Religious Education teachers act as students' guides and counselors to develop an attitude of state life and socialize in a pluralistic society in building togetherness without any form of identity politics.